Designing payload and spaceflight operations for plants from extreme terrestrial environments - Zupanska, Agata K.; Lockwood, Emily; Zhang, Ye; Haveman, Natasha J.; Carver, John A.; Spern, Charles W.; Senyk, Emily; Richards, Jeffrey T.; Koss, Lawrence L.; Dimapilis, Dinah I.; McDaniel, Stuart F. (Frontiers in Space Technologies, 2024)
Terrestrial plants from the edges of the limits of life are likely to harbor genes that confer an advantage in human space exploration. These plants are seemingly capable of performing mission critical functions in spaceflight and on extraterrestrial farms, while informing directed gene manipulation in target plant species. However, their adaptations to physiologically extreme habitats may hinder efficacy of routine laboratory techniques established for model plants. Here we present the development of Antarctic moss Ceratodon purpureus payload and flight operations for the ARTEMOSS experiment to the ISS astute of limited physical space and crew time. We demonstrate that the hydrophobic surface of Antarctic moss impedes chemical tissue fixation and precludes usage of RNAlater coupled with payload hardware deployed in standard plant spaceflight experiments. We show that deep-freezing the moss tissue on Petri plates provides adequate tissue fixation and allows for extraction of high-quality RNA suitable for gene expression profiling. We replaced hardware with stacks of Petri plates housing Antarctic moss and chemical fixation with deep-freeze in cryogenic GLACIER freezer. Our design can be translated to other plant species, expanding current techniques of experimentation with plants from extreme terrestrial environments aimed toward advancing human space exploration.